Approach to the calculation of the probability of cochannel interference for PCS/PCN cellular planning - Koshi, V; Edwards, D; Street, A (1996)
A methodology for prediction of outage probability and probability of cochannel interference for PCN/PCS is described. The approach enables a comparison of the relative performance of different systems under varying conditions. DCS1800 and PCS1900 results illustrate the impact of implementation options on the outage probability, probability of cochannel interference, system capacity and cost.